Enhancing the Feed Capacity of Horticulture Agro-Ecosystem Through Technology for Goat Production - Ginting, Simon P (Indonesian Animal Sciences Society, 2011)
The availability of feed and their efficiency of use throughout the year represent the most important constraint affecting the productivity of animals in any agro-ecosystems. Beside being the largest contributor to the total production cost, logistically feeds need to be available on a daily basis across the animalâs life time. In order to be competitive, goat production system must be directed toward the optimum utilization of inconventional feedstuffs such as crop residues and agro-industrial by-products. The horticulture crops provide various crop-residues and by products from the processing of its main products. These biomass are potential feedstuffs that could be used to support the production of goats. The processing of passion fruits (Passiflora edulis) yield by products such as fruit shells and seeds. These products are good energy and protein sources for growing goats. Oriental radish (Raphanus sativus) by-products composed by damaged root parts and culls have high digestible energy and low ether extract content, but have very high moisture content. The pineapple by-products composed by the peel and bagasse of the fruit could be used as energy source for goats. Other horticulture by-products or residues such as citrus pulp, abandoned citrus fruit, forages from Ipomea batatas are of great potential as feeds for goat production. Preserving technology like ensiling could be implemented in utilising those biomass categorized as wet by-products such as pineapple and oriental radish by-products. The technology of complete feed is an effective means in utilizing some of those products with relatively low palatability or to increase its inclusion level in diets. Introducing shade-tolerant forage species as intercrops such as Stenotaphrum secundatum,Â Brachiaria humidicola and Arachis pintoi in the citrus plantation should increase feed capacity of the area. The multi-purpose trees such as Indigofera sp. and Calliandra calothyrsus both are adaptable to the high altitude area are valuable feeds due to their high nutritional quality. Generation of technology that could maximize the utilization of those biomass as feeds for goat production is necessary. Some technologies that are relevant to that purposes including: 1) ensiling with appropriate inoculants that create optimal fermentation to preserve the product and to prolong the aerobic stability of the silages; 2) ensiling with appropiate absorbants for maximum effluent retention, intake and preference of the silage; 3) the utilization of fibrolytic bacteria; 4) utilization of fibrolytic enzymes in complete feed; and 5) supplementation strategy to optimize the rumen function for maximum utilization of basal diets. Because most of the feedstuffs mentioned above relatively vary in their nutritional quality and quantity, it is suggested that feed budget system, which is based on the availability of feed rather than the feeding standard system which is based on the animalâs nutrient requirement is a more relevant feeding system for goat production. Key words: Feeds, horticultures, technology, goats